The winding roads to adulthood: A twin study. Issue 4 (11th December 2021) - Rimfeld, Kaili; Malanchini, Margherita; Packer, Amy E.; Gidziela, Agnieszka; Allegrini, Andrea G.; Ayorech, Ziada; Smith‐Woolley, Emily; McMillan, Andrew; Ogden, Rachel; Dale, Philip S.; Eley, Thalia C.; Plomin, Robert
Abstract: Aims: Here we report the results of the first systematic investigation of genetic and environmental influences on 57 psychological traits covering major issues in emerging adulthood such as aspirations, thoughts and attitudes, relationships and personality. We also investigate how these traits relate to physical and mental health, educational attainment and wellbeing. Materials & Methods: We use a sample of nearly 5000 pairs of UK twins aged 21–25 from the Twins Early Development Study. We included 57 measures of traits selected to represent issues in emerging adulthood (EA) such as aspirations, thoughts and attitudes, life events, relationships, sexual and health behaviour and personality. We also included measures related to what are often considered to be the core functional outcomes even though here we refer to the data collected at the same time: adverse physical health, adverse mental health, wellbeing, and education. Results: All 57 traits showed significant genetic influence, with an average heritability of 34% (SNP heritability 10%). Most of the variance (59% on average) was explained by non‐shared environmental influences. These diverse traits were associated with mental health (average correlation 0.20), wellbeing (0.16), physical health (0.12) and educational attainment (0.06). Shared genetic factors explained the majority of these correlations ( 50%). Together, these emerging adulthood traits explained on average 30% of variance in the outcomes (range = 8% to 69%), suggesting that these traits relate to the outcomes additively. Discussion & Conclusions: We conclude that even as the majority of individual differences in EA traits is explained by non‐shared environmental factors, genetic influence on these traits is still substantial; the environmental uncertainties of emerging adulthood in the 21st century do not diminish the importance of genetics. As adolescents travel down long and winding roads to adulthood, their trip is substantially influenced by genetic proclivities that nudge them down different paths leading to different destinations. Abstract : Univariate twin analyses of additive genetic (A), shared environmental (C), and non‐shared environmental (E) components of variance for emerging adulthood traits.